Implementing a Virtual Learning Environment to Enhance Modeling skills and Collaboration in a Pre-service Teacher Education Science Program: Students' Ideas about a Blended e-Learning Approach. - Nicolaidou, Iolie; Nicolaou, Christiana T.; Constantinou, Constantinos P. (My University, 2005)
This paper reports on a research study targeted at a) the development of modeling skills of pre-service teachers, through the use of Stagecast Creator and b) the enhancement of collaboration among students, through the use of WebCT. Participants were 20 pre-service teachers who attended a science course at the University of Cyprus (spring semester 2004). A blended e-learning approach was used, as the course incorporated e-learning through the use of WebCT combined with face-to-face teaching. The study took advantage of platform functions for presentation of information, synchronous and asynchronous communication and students' access to models developed by other students for assessing and refining them. Means of data collection include students' reflective journals, reports of the synchronous discussions, and a questionnaire. Data analysis indicates that students believe that the blended e-learning approach critically enhanced the development of modeling skills and the collaboration among them.
Keywords: Collaboration; Students; Teachers; Collaboration; Pre-Service Teacher Education